Policies and Practices Recommended in Feeding Older Infants (more than 6 months and under 1 year) and Young Children (1 to 2 years) in Indonesia - R. Sutedjo (Indonesian Pediatric Society, 1974)
In general breast milk production starts biologically to decrease by the infant's age of approximately 5 months, so that supplementary feeding becomes necessary by that age. In fact, at the age of 2 months supplementation can already be started once or twice daily in the form of a biscuit (20 gm) soaked in milk or tea or in the form of fruits either banana (50 gm), papaya (50 gm) or orange juice (50 gm).